The Frequency of Deixis Used in “I Have A Dream” by Westlife - Tarigan, Ayu Sarmila; Lisdawati, Ida (PROJECT (Professional Journal of English Education), 2025)
Deixis is a term used to represent a word or phrase that directly relates to entities such as objects, processes, attributes, and circumstances. The importance of this research is to find out the frequency and the percentage of deixis that appear in the lyrics of songs to be analyzed by researchers. In addition to knowing this analysis also serves to find out the lyricist's point of view of the song from each deixis contained in the song. The method used in this study was descriptive qualitative. Which data used was based on the data that has been available on the song "I have a dream" by Westlife. Based on the results of the analysis on the lyrics of the song that has been done by researchers, it can be concluded that in the song "I have a dream" by Westlife the type of deixis that has the highest percentage is person deixis which is as much as 72%. While the results of the number of temporal and spatial deixis are the same, which is 14% for temporal deixis and 14% for spatial deixis.